2012
DOI: 10.1021/cn300048q
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes: Artificial Nanomaterials to Engineer Single Neurons and Neuronal Networks

Abstract: In the past decade, nanotechnology applications to the nervous system have often involved the study and the use of novel nanomaterials to improve the diagnosis and therapy of neurological diseases. In the field of nanomedicine, carbon nanotubes are evaluated as promising materials for diverse therapeutic and diagnostic applications. Besides, carbon nanotubes are increasingly employed in basic neuroscience approaches, and they have been used in the design of neuronal interfaces or in that of scaffolds promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 73 publications
0
81
0
1
Order By: Relevance
“…1,2 For instance, cultured neurons have been tested on different nanosurfaces by several investigators. 3,4 Structured materials which facilitate dendrite development, adhesion, and signaling may promote better understanding of neuronal repair from pathological conditions and present novel therapeutic strategies. 5,6 Another example of the ramified cell is the glomerular podocyte.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 For instance, cultured neurons have been tested on different nanosurfaces by several investigators. 3,4 Structured materials which facilitate dendrite development, adhesion, and signaling may promote better understanding of neuronal repair from pathological conditions and present novel therapeutic strategies. 5,6 Another example of the ramified cell is the glomerular podocyte.…”
Section: Introductionmentioning
confidence: 99%
“…It can also be speculated that the high electrical conductivity of graphene is an important factor that can lead to better growth and maturation of hippocampal neurons. It is well reported that electrical stimuli play a pivotal role in the nervous system, and it has been shown that the electrical conductivity of carbon nanotubes promotes neuron growth [42,43]. Also, previous reports showed that two-dimensional graphene film can act as a transparent electrode to electrically stimulate cells [13].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prostheses for monitoring brain activity were developed using interfaces based on nanotube architecture (Stankova et al 2014). Fabbro et al (2012) recently demonstrated the alteration of various hippocampal neurons responses by the CNTs substrates in cultures. This observation highlighted the exceptional ability of the CNTs substrate to interfere with nerve tissue growth; they confirmed the hypothesis that CNT scaffolds promote the development of immature neurons isolated from the neonatal rat spinal cord and maintained in vitro.…”
Section: Carbon Nanotubes As Interfaces For Neural Prostheticsmentioning
confidence: 99%
“…Development of future strategies for tissue repair in order to promote functional recovery after brain damage is one of the main aims of nanotech studies (Fabbro et al 2012). CNTs based technologies are emerging as particularly innovative tools due to their ability to interface neuronal circuits, synapses and membranes (Sakhtianchi et al 2013), as well as due to the outstanding physical properties of these nanomaterials.…”
Section: Neuroregeneration Of Brain Circuitsmentioning
confidence: 99%